'A flight over the study area': ecological ontologies in doctoral thesis acknowledgments. Issue 4 (4th July 2021) - Kelly, Frances; Manathunga, Catherine
ABSTRACT: The formation of emerging doctoral scholarly identities has received significant attention in recent Education research, some of which is situated within the spatial turn that seeks to understand the impact of space and place upon identity and pedagogy. In this research project, involving analysis of PhD thesis acknowledgements written in 1980, we began with focusing on how these texts illustrated the social, epistemological and spatial aspects of doctoral scholarly identity formation. However, our encounters with these evocative data challenged us to enlarge our thinking about the relationship between a scholarly identity, place and things, and offered possibilities to apply the concepts of the 'placeful university' and 'ecological ontology' to our analysis. These concepts offer an alternative way of thinking about mind and matter in doctoral education that takes us beyond Cartesian dualism, undermining and decentring the traditional and neoliberal university's construct of the heroic individual researcher.